Dead Sea Scrolls Fragments in the Museum Collection - Tov, ʿEmanuʾel (Publications of Museum of the Bible Ser, 2016)
‎Contents -- ‎Preface (Pattengale) -- ‎List of Tables -- ‎List of Figures -- ‎List of Abbreviations -- ‎Introduction to the Museum Collection of Dead Sea Scrolls Fragments -- ‎Chapter 1. Introduction, Text Editions, the Collection of the Museum of the Bible, Textual and Orthographic Character, Relation to Other Fragments from the Judaean Desert (Tov) -- ‎Chapter 2. Paleographical and Physical Features of the Dead Sea Scrolls in the Museum of the Bible Collection: A Synopsis (Davis) -- ‎Zuckerman, Levy and Lundberg -- ‎Chapter 4. The Process and Goal of Research (Duke)